MIMO SAR Operation Modes and Techniques - Younis, Marwan; López-Dekker, Paco; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2014)
MIMO SAR stands for systems utilizing multiple-receive and multiple-transmit channels. The trade-space for SAR includes the instrument and antenna parameters taking into consideration the techniques, i.e. the operation modes of the radar. The purpose of exploring this trade-space is to improve and optimize the performance of the system, described through the performance parameters. The aim of this paper is to give examples showing that MIMO SAR offers new and unexpected ways of trading the system and performance parameters versus each other. Adequately exploring the trade-space yields a high flexibility and allows to simultaneously improve several performance parameters; conventional single channel SAR systems do not have the same flexibility. The content of this paper is considered novel in the sense that it deals with highly advanced techniques for SAR.
DLR Import::2019-04-03